How grammar can be best taught - Leão, Luciana Braga Carneiro (Domínios de Lingu@gem, 2012)
In the field of language teaching, especially in second language teaching, teachers and researchers are constantly concerned with using the most efficient ways to provide knowledge to learners leading to acquisition. This article aims to analyze form-focused instructional options regarding grammar teaching, in light of the computational model for second language acquisition, and discuss if there is a best way to teach grammar and what it is. For that, firstly, the instructional possibilities are presented, in their macro and micro-options. Secondly, discussions on whether we should select or not and on if we could balance different options throughout a lesson are carried. Finally, sample material is provided in order to present possible ways to conduct a grammar lesson.